A-24, a steroidal saponin from Allium chinense, induced apoptosis, autophagy and migration inhibition in p53 wild-type and p53-deficient gastric cancer cells. (1st October 2021) - Xu, Jingwen; Wang, Yihai; Wang, Yi; Wang, Zhe; He, Xiangjiu
Abstract: Allium chinense is a vegetable with nutrition and unique flavor, and it is used as traditional Chinese medicine. We previously reported that the active compound A-24 induces apoptosis and autophagy in p53 wild-type gastric cancer cells through the PI3K/Akt/mTOR pathway. Our present work indicates that A-24 also has a significant proliferation inhibition effect on p53-deficient KATO-III cells, and the p53 status did not affect A-24 induced migration inhibition, but negatively controlled the occurrence of autophagy. We also found that the accumulation of reactive oxygen species (ROS) mediated A-24 induced apoptosis is p53-independent. Besides, p-Akt was not downregulated by A-24 in p53-deficient gastric cancer cells. Taken together, our results indicate that A-24 induced apoptosis and autophagy via the ROS-PI3K/Akt/mTOR pathway in p53 wild-type gastric cancer cells and through the ROS-mTOR pathway in p53-deficient gastric cancer cells. Our study recommended A-24 as a promising future phytotherapeutic candidate for gastric cancer treatment. Graphical abstract: Image 1 Highlights: ● A-24 induced p53-independent apoptosis in gastric cancer cells. ● A-24-induced ROS accumulation is independent of p53. ● A-24-induced autophagy is negatively regulated by p53. ● A-24 induced p53-independent migration inhibition.